Distributed semi-clustering protocol for large-scale wire-less sensor networks - H. Wasmi, Mohanad; Aliesawi, Salah; Jasim, Wesam (International Journal of Engineering and Technology, 2018)
Conservation of energy is one major issue in the deployment of Wireless Sensor Networks (WSNs). The power resources of the sensor nodes are significantly restricted and these nodes are deployed in remote places. Communication protocols must be designed carefully in order to achieve the efficient utilization of the limited energy of sensor nodes. Clustering the nodes is the best technique to achieve this goal and improve the lifetime of the network. Many protocols have been proposed to prolong the lifetime of the network. Low- Energy Adaptive Clustering Hierarchy (LEACH) is one of the most famous of clustering protocols. LEACH transmits data directly from Cluster Head (CH) to the Base Station (BS), thereby far away nodes from BS dies early. In this paper, we propose a new routing protocol called Distributed Semi-Clustering Protocol (DSCP), which is more suitable for long-scale transmission in WSNs. Instead of using Direct Transmission (DT) to send data of CH to BS, DSCP uses Multi-Hop (MH) communication with minimum energy cost from each CH to reach BS. Finally, the Dijkstra algorithm is employed in DSCP between CHs to efficiently search for the optimal path. The simulation results show the significant improvement of our proposal compared to other clustering protocols, and it has a longer network lifetime and more extended stability period.Â